Cardinal Mammographic Signs of Malignant Breast Tumor - Aracki Trenkić, Aleksandra; Jevremović, Aleksandar; Babić, Rade (Medical Word, 2026)
Cardinal mammographic signs of breast tumors can be categorized into three groups: first group: characteristics of tumor shadow; second group: characteristics of calcifications; third group: characteristics of other accompanying mammographic signs. The goal of the work is to show the cardinal mammographic signs of a malignant breast tumor, while the material of the work consists of 1,300 screening mammograms, performed between January and May 2025, in the Radiology Center of the University Clinical Center in Niš, in women from Rasa, Jagodina, Blace and Prokuplje, and literal reports. The results of the work are illustratively presented in three patients. The authors conclude that the mammographic cardinal signs of a malignant breast tumor represent those X-ray changes that, once visualized on mammograms, point to an objective indication of breast disease, but should by no means be accepted as a substitute for a biopsy of visualized changes in the glandular parenchyma of the breast.
Keywords: mammography; tumor; breast